Risk Factors of Recurrence of Acute Pancreatitis: A Retrospective Research - Kun Song; Cuirong Guo; Changluo Li; Ning Ding (Turkish Journal of Gastroenterology, 2021)
Background: Acute pancreatitis (AP) was one of the most common disorders of acute hospital admission with significant morbidity and mortality. Some of the patients experienced recurrent attacks of AP, leading to recurrent acute pancreatitis (RAP) and poor clinical outcomes. The association of clinical and laboratory variables with recurrence of AP were analyzed to evaluate the risk of RAP. Methods: All patients with AP admitted in the hospital between January 2017 and December 2019 were included in this study. Clinical and laboratory variables were analyzed and risk factors were identified by multivariate logistic regression. The receiver operating characteristic (ROC) analysis for predicting recurrence of AP was performed. Results: A total of 834 AP patients, including 671 in the non-RAP group and 167 in the RAP group, were enrolled in the study. There were significant differences in age, sex, body mass index (BMI), history of biliary surgery, cholelithiasis, diabetes, triglyceride (TG), high-density lipoprotein, and cholesterol between the non-RAP group and the RAP group. Two independent variables were identified as risk factors for recurrence of AP: TG (P = .007, odds ratio [OR] = 1.101, 95% CI, 1.025-1.183), and BMI (P = .032, OR = 1.094, 95% CI, 1.009-1.086). The area under the curve of ROC analysis of TG and BMI were 0.702 (95% CI, 0.655-0.749) and 0.593 (95% CI, 0.538-0.647). The best threshold for TG and BMI to anticipate recurrence of AP were 5.9 (sensitivity0.763, specificity 0.595) and 28.24 (sensitivity 0.302, specificity 0.844). Conclusion: TG and BMI were identified as independent predictors for recurrence of AP. A TG level of 5.9 mmol/L could be a clinical guide for the target level of lowering TG therapy in AP patients with hypertriglyceridemia. Cite this article as: Song K, Guo C, Li C, Ding N. Risk factors of recurrence of acute pancreatitis: A retrospective research. Turk J Gastroenterol. 2021;32(11):971-978.